PERTUMBUHAN DAN HASIL BAWANG MERAH (Allium ascalonicum L.) PADA BEBERAPA JENIS MEDIUM TANAM DENGAN TEKNIK VERTIKULTUR - Prayogi, Fajar; Islan, Islan; Ariani, Erlida (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2019)
Red onion plant is one of the annual plant that has important economic value. This plant is usually used as cooking spice and traditional medicine. The low productivity of red onion plant is due to limited availability of agricultural land. Efforts for development of red onion need to be done by applying verticultural farming system. This study aimed to look at the effect of kind of planting medium with verticultural technique on growth and yield of red onion plant and to get the best kind of planting medium. The field experiment was conducted in the Faculty of Agriculture experiment station Riau University located in Pekanbaru from August to October 2018. The design used was a completely randomized design (CRD) with 6 replications. The factor was kind of planting medium, which were husk charcoal, cocopeat and sawdust. Parameters observed were plant height, number of leaves, number of tubers, tuber diameter, weight of tuber, dry weight of tuber worth storage. Data obtained from this study were analized statistically by using the analysis of variance (ANOVA) and further tested by further testing (DNMRT) level of 5%. The results showed that the giving of cocopeat planting medium can increase plant height and diameter of red onion plant. The giving of husk charcoal planting medium can increase the number of tuber. The giving of sawdust planting mediumtend to increase thenumber of leaves, wet weight and dry weight of red onion tuberKeywords: Red onion plant, growth, husk charcoal, cocopeat, sawdust